Thymic depletion and peripheral activation of class I major histocompatibility complex-restricted T cells by soluble peptide in T-cell receptor transgenic mice. - Mamalaki, C; Norton, T; Tanaka, Y; Townsend, A; Chandler, P; Simpson, E; Kioussis, D (1992)
Injection of mice transgenic for a class I major histocompatibility complex-restricted T-cell receptor with a soluble peptide antigen from influenza virus nucleoprotein results in clonal depletion of double-positive immature thymocytes in the thymus and activation of mature T cells in the periphery, accompanied by a transient up-regulation of the T-cell receptor and CD3 and CD8 coreceptor molecules.